An epidemiology study for tuberculosis in the Philippines from 1960 to 2019 - Angel Mae Frias Luga; Kathleen Laum Cabanlit; Jamerah Baniaga Sidic; Ralf Benjo Goder Morilla; Chin-Chin Jimenea Demayo; Cesar Guinanao Demayo (International Journal of Public Health Science (IJPHS), 2023)
Tuberculosis has long been a public health threat in the Philippines, however, there is still no recent trend study for this country’s morbidity and deaths from the said infectious disease. With that, an age-, sex-, and region-specific morbidity and mortality trend study for tuberculosis in the Philippines was conducted for these types of studies significantly help in the surveillance and control of diseases. Data from the Philippine Health Statistics from 1960 to 2019 was mined to assess the morbidity and mortality rates from tuberculosis in terms of age, sex, and regions, which were then visualized through graphs. The results revealed that the mortality rate trend for tuberculosis in the Philippines from 1960 to 2019 declined over time. Also, as for the sex-specific mortality rate trend, it was observed that males consistently had a higher death rate in comparison to females through the years. As for the age-specific mortality rates, it increased with age, showing the direct proportionality of age to the rate of deaths. Lastly, for the region-specific morbidity and mortality rates, it was observed that Region V (Bicol Region) has the highest morbidity rate. On the other hand, Region VI (Western Visayas) has the highest mortality rate from tuberculosis.